Analisis Framing Budaya dalam Serial Video Game Ghost of Tsushima - Muhammad Taufik Akbar; Dosen Pembimbing (Bandung Conference Series: Public Relations, 2024)
Abstract. This research analyzes the framing in the video game "Ghost of Tsushima" to explore how Japanese culture is conveyed to players. Using qualitative research methods and the framing analysis approach of William A. Gamson and Andre Modigliani, this study identifies cultural elements in each game scene. Data were analyzed using Gamson and Modigliani's condensing symbol theory, including framing devices (metaphors, catchphrases, exemplars, depiction, visual images) and reasoning devices (roots, appeals to principle, consequences). The game presents 13th century Japanese samurai culture against the backdrop of the Mongol invasion, depicting the conflict between honor and revenge and the struggle to maintain cultural identity. The results show that the game shapes players' understanding of samurai values through the metaphor of "Samurai as Ghosts," catchphrases reflecting Jin Sakai's changing identity, and exemplars of his internal conflicts. The visualization of the beautiful yet war-torn Tsushima reinforces the emotional atmosphere and complex narrative. Jin's transformation from a traditional samurai to a "ghost samurai" emphasizes the importance of adaptation in the face of challenges. Overall, "Ghost of Tsushima" successfully uses framing theory to present a rich and meaningful narrative, educating players about the values of samurai culture and deepening understanding of Japanese history and culture. Abstrak. Penelitian ini menganalisis framing dalam video game "Ghost of Tsushima" untuk mengeksplorasi bagaimana budaya Jepang disampaikan kepada pemain. Menggunakan metode penelitian kualitatif dan pendekatan analisis framing William A. Gamson dan Andre Modigliani, penelitian ini mengidentifikasi elemen budaya dalam setiap scene game. Data dianalisis menggunakan teori condensing symbol dari Gamson dan Modigliani, mencakup framing devices (metafora, catchphrases, exemplars, depiction, visual images) dan reasoning devices (roots, appeals to principle, consequences). Game ini menyajikan budaya samurai Jepang abad ke-13 dengan latar belakang invasi Mongol, menggambarkan konflik antara kehormatan dan balas dendam serta perjuangan mempertahankan identitas budaya. Hasil penelitian menunjukkan bahwa game ini membentuk pemahaman pemain tentang nilai-nilai samurai melalui metafora "Samurai sebagai Hantu," catchphrases yang mencerminkan perubahan identitas Jin Sakai, dan exemplar konflik internalnya. Visualisasi Tsushima yang indah namun hancur oleh perang memperkuat atmosfer emosional dan narasi kompleks. Transformasi Jin dari samurai tradisional menjadi "samurai hantu" menekankan pentingnya adaptasi dalam menghadapi tantangan. Secara keseluruhan, "Ghost of Tsushima" berhasil menggunakan teori framing untuk menyajikan narasi yang kaya dan bermakna, mendidik pemain tentang nilai-nilai budaya samurai dan memperdalam pemahaman tentang sejarah dan budaya Jepang.